Efecto analgésico intraoperatorio del clorhidrato de lidocaína en ovariosalpingohisterectomia en perras - Aveiga Dueñas, Diana Elizabeth (2016)
This investigation has been made at the Veterinary Clinic “Boxer” , the analgesia effect of the lidocaine hydrochloride in a 2% intravenously was evaluated at a dose of 2mg/kg/hour in sodium chloride solution at 0.09%, 20 female dogs had an ovary salpingohysterectomy,10 of them received analgesic and the rest of them were operated without any kind of intraoperative analgesia, physiological variables heart rate were used as indicators , breathing frequency, pulse oximetry (oxygen saturation), temperature, capillary refill time and arterial pressure, which they were recorded using multiparameter monitor in four surgical time: medial incision, tissue manipulation, extraction of ovaries, uterus, fallopian tube and in the final sutures, it was used technical statistical comparison of groups, lidocaine hydrochloride proved to be effective in pain control in the four time, significant difference p<0,05% was observed in heart rate , breathing frequency, temperature, oxygen saturation, mean arterial pressure and capillary refill time, the controlled group showed particularly high tachycardia at the time of extraction of ovaries with 206.7 bpm and oxygen saturation below 95 % was recorded in the four times the least of 93.3 % for the control group; the economic cost is below the $ 0.029 per ml and a total of US $ 0.29 in the 10 dogs used in the treatment group